A new dibenzoylhydrazine with insecticidal activity against Anopheles mosquito larvae. Issue 7 (4th December 2012) - Morou, Evangelia; Lirakis, Manolis; Pavlidi, Nena; Zotti, Moises; Nakagawa, Yoshiaki; Smagghe, Guy; Vontas, John; Swevers, Luc
Abstract BACKGROUND Dibenzoylhydrazine (DBH) compounds have been applied successfully as environmentally safe insecticides against lepidopteran larvae and ground‐dwelling coleopterans, but their potential to combat mosquito larvae is largely unknown. Here, toxicity tests of three commercial DBHs (tebufenozide, methoxyfenozide and halofenozide) and one experimental DBH (KU‐106) against larvae of Anopheles gambiae, the major vector for human malaria, are reported. RESULTS Based on calculated median larvicidal concentration (LC50) values at 5 days of treatment, KU‐106 (760 nM) showed an activity against Anopheles larvae similar to that of commercial halofenozide. Induction of the early‐late gene hr3 and docking studies of DBHs in the ligand‐binding pocket of the modelled Anopheles ecdysone receptor indicated that toxicity is caused by the activation of the ecdysone regulatory cascade causing a premature lethal moult. CONCLUSIONS As a result of the similar toxicity exhibited by the experimental compound KU‐106 to that shown by commercial products, the present study demonstrated that the use of DBH compounds to combat harmful dipteran insects, such as mosquitoes, remains unexplored and invites further systematic toxicity tests using other derivatives of the DBH class of compounds.© 2012 Society of Chemical Industry